Hypertrophic cardiomyopathy: the future of treatment. (9th January 2020) - Tuohy, C. Vaughan; Kaul, Sanjiv; Song, Howard K.; Nazer, Babak; Heitner, Stephen B.
Abstract: Hypertrophic cardiomyopathy (HCM) is a heterogeneous genetic disorder most often caused by sarcomeric mutations resulting in left ventricular hypertrophy, fibrosis, hypercontractility, and reduced compliance. It is the most common inherited monogenic cardiac condition, affecting 0.2% of the population. Whereas currently available therapies for HCM have been effective in reducing morbidity, there remain important unmet needs in the treatment of both the obstructive and non‐obstructive phenotypes. Novel pharmacotherapies directly target the molecular underpinnings of HCM, while innovative procedural techniques may soon offer minimally‐invasive alternatives to current septal reduction therapy. With the advent of embryonic gene editing, there now exists the potential to correct underlying genetic mutations that may result in disease. This article details the recent developments in the treatment of HCM including pharmacotherapy, septal reduction procedures, mitral valve manipulation, and gene‐based therapies.